2016
DOI: 10.1088/1475-7516/2016/05/029
|View full text |Cite
|
Sign up to set email alerts
|

Chiral charge erasure via thermal fluctuations of magnetic helicity

Abstract: We consider a relativistic plasma of fermions coupled to an Abelian gauge field and carrying a chiral charge asymmetry, which might arise in the early Universe through baryogenesis. It is known that on large length scales, λ 1/(αµ 5 ), the chiral anomaly opens an instability toward the erasure of chiral charge and growth of magnetic helicity. Here the chemical potential µ 5 parametrizes the chiral asymmetry and α is the fine-structure constant. We study the process of chiral charge erasure through the thermal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…As emphasized in Ref. [17], it is generally difficult to produce a very strong primordial magnetic field starting from a small baryon asymmetry at the level of n B /s ∼ 10 −10 . On the other hand, Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As emphasized in Ref. [17], it is generally difficult to produce a very strong primordial magnetic field starting from a small baryon asymmetry at the level of n B /s ∼ 10 −10 . On the other hand, Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This violation is expressed by the current conservation equations, Many studies have investigated the connection between a primordial magnetic field (PMF) and the baryon asymmetry of the universe (BAU). Broadly speaking, the literature falls into three categories: PMF-from-BAU [15][16][17], BAU-from-PMF [18][19][20][21][22][23][24][25], and co-evolution [26][27][28][29][30][31][32][33]. As emphasized in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Among the earliest works, Joyce and Shaposhnikov [17] showed that a helical hypermagnetic field can arise in the symmetric phase of the EW plasma from a preexisting lepton asymmetry carried by the right-chiral electron [18] (see also Refs. [19,20]). This work was soon extended by Giovannini and Shaposhnikov [21][22][23][24] to consider the generation of baryonnumber isocurvature fluctuations from a preexisting stochastic hypermagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Possible mechanisms to explain cosmic magnetogenesis may be divided into two main categories: cosmological scenarios predict that magnetic fields were generated through processes taking place in the early universe, such as inflation [1][2][3][4], electroweak [5][6][7][8] or QCD phase transitions [9][10][11][12], and leptogenesis [13,14], among others; in astrophysical scenarios the fields would be created during the later stages of evolution of the universe, for example during structure formation [15] or even thereafter [16].…”
Section: Introductionmentioning
confidence: 99%